Enhancing dynamism in SMEs and entrepreneurship in Korea - Jones, Randall S.. (OECD Publishing, 2018)
Making SMEs and start-ups a driver of growth and job creation requires a number of policies to improve the performance of SMEs, whose labour productivity in the manufacturing sector has fallen to less than a third of that in large companies. The large-scale support for SMEs should shift from supporting the survival of firms to raising productivity. Measures to accelerate SMEs' take-up of new technology and increase their participation in international trade would boost productivity and inclusive growth. Given the chronic labour shortages facing SMEs, reforming the education system to reduce labour market mismatch is a priority. Relaxing the regulatory burden and government control would allow innovative SMEs to create new products and services. Entrepreneurship is lagging, reflecting a higher fear of failure and a lack of skills in Korea. Upgrading entrepreneurship education and lowering the personal costs faced by entrepreneurs who fail would be beneficial. A greater role for venture capital, in part by activating the M&A market to allow investors to recuperate their funds, would encourage firm creation. This Working Paper relates to the 2018 OECD Economic Survey of Korea (www.oecd.org/eco/surveys/economic-survey-korea.htm)
Keywords: Economics; Korea, Republic of